Correlação entre estrutura e atividade em complexos de cobre biomiméticos a LPMO para degradação de biomassa lignocelulósica - Conciani, Gabrielle Rodrigues (Universidade Federal de São Carlos, 2026)
Correlation between structure and activity in LPMO biomimetic copper complexes for degradation of lignocellulosic biomass. The transition toward a more sustainable economy has driven the search for more efficient technologies for the conversion of lignocellulosic biomass into biofuels. In this context, lytic polysaccharide monooxygenases (LPMOs) stand out for their ability to promote the oxidative cleavage of glycosidic bonds in crystalline regions of cellulose. This activity is conferred by the enzyme's catalytic site, which features a copper atom coordinated by two histidine residues, one of them in a histidine brace coordination mode. Taking this active site as inspiration, this work aimed to synthesize, characterize, and evaluate the catalytic activity of biomimetic copper(II) complexes, with emphasis on the development of a novel L-proline-derived complex (CuAL), and to compare its performance with two other LPMO-mimetic complexes: CuPol and CuPTB. The AL ligand was synthesized from L-proline and characterized by NMR, HRMS, and IR spectroscopy. Its copper(II) complex was obtained by reaction with Cu(ClO4)2·6H2O and characterized by UV-Vis, IR, elemental analysis, XPS, cyclic voltammetry, and EPR. XPS data revealed shifts in the binding energies of nitrogen and carbon atoms consistent with metal coordination, indicating electron donation from the donor sites and π-backdonation from the metal to the ligand. The catalytic activity of the complexes was evaluated using different substrates. In assays with 4-nitrophenyl-β-D-glucopyranoside, CuAL exhibited superior performance (Abs 405 nm ~1.0), followed by CuPol (~0.7) and CuPTB (<0.3). In total cellulolytic activity assays carried out in the absence of additives (H2O2 or ascorbate), CuAL again stood out, releasing 0.14 mg/mL of glucose equivalents without H2O2, a value higher than those obtained for CuPol (0.05 mg/mL) and the enzymatic extract (<0.05mg/mL). A synergistic effect between CuPol and the enzyme was observed, with a release of 0.10 mg/mL. Assays with carboxymethylcellulose indicated endoglucanase-like activity for CuAL, while tests with crystalline cellulose were negative, suggesting preferential action on amorphous substrates. The addition of H2O2 and ascorbate to the filter paper assays completely inhibited CuAL activity, indicating that the complex acts via hydrolysis rather than oxidative pathways. The results demonstrated that the structure–activity correlation provides highly relevant insights for catalyst development. The substitution of the carboxylate group in CuPol by the primary alcohol group in CuAL significantly altered the reactivity profile of the complex. While CuPol exhibits a high density of ligand centered radicals and operates preferentially through H2O2-dependent oxidative pathways, CuAL displays significant catalytic activity even in the absence of oxidants. This suggests that the coordinated alcohol group favors direct hydrolytic mechanisms, possibly through water molecule activation or more favorable interactions with cellulose hydroxyl groups. The lability of the Cu–O bond in CuAL and its lower tendency towards polymerization in solution contribute to greater accessibility of the metal site to the substrate, while the absence of stabilized ligand-centered radicals limits protection against oxidative damage and directs catalysis toward hydrolytic pathways.
Correlation between structure and activity in LPMO biomimetic copper complexes for degradation of lignocellulosic biomass
Keywords: LPMO; Correlação estrutura atividade; Structure-activity correlation; Complexos de cobre biomiméticos; Biomimetic copper complexes; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA; 7. Energia limpa e acessível